Formation of germanium oxynitride as buffer layer on germanium substrate / Soh Wee Chen - Soh, Wee Chen (2018)
Thermal oxynitridation process was used to grow germanium oxynitride, GeON thin films as a buffer layer on the germanium substrates in nitrous oxide (N2O) gas ambient at several temperatures: 400 °C, 500 °C and 600 °C. The physical and chemical properties of the buffer layers formed were characterized and investigated using X-ray diffraction (XRD) and Fourier transform infrared (FTIR). The XRD patterns showed the crystallinities that belongs to the germanium dioxide (GeO2), gamma-germanium nitride (γ-Ge3N4) and digermanium dinitrogen oxide (Ge2N2O). Digermanium dinitrogen oxide was formed at 600 °C and its peaks were detected at 31.58° and 65.92° corresponding to planes (110) and (220) respectively in XRD pattern. Meanwhile, peaks indicating the presence of germanium oxide and gamma-germanium nitride were found in XRD pattern for all the samples. GeO2 were detected in XRD patterns at 28.9°, 35.5°, 42.6° and 47.0° corresponding to (110), (111), (200) and (210). γ–Ge3N4 were also found in the XRD patterns at 38.83°, 47.97° corresponding to planes (110), (111). FTIR detected the Ge2N2O absorption peak at 800 cm-1 at 600 °C sample, thus confirming the formation of Ge2N2O on the germanium substrate at 600 °C.